Interaction between seawater carbon dioxide dynamics and stratification in shallow coastal waters: A preliminary study based on a weekly validated three-dimensional ecological model - Xiong, Bing; Yano, Shinichiro; Komai, Katsuaki; Saito, Naoki; Komori, Hiroto; Chi, Baixin; Hao, Lin; Nakayama, Keisuke (Frontiers in Marine Science, 2022)
Shallow coastal waters (SCWs) have attracted wide attention in recent years due to their strong carbon sequestration capacity. However, the complex carbon dioxide (CO2) dynamics in the water column makes it difficult to estimate the air–water CO2 fluxes (FCO2) accurately. We developed a numerical model of CO2 dynamics in water based on field measurements for a typical stratified semi-enclosed shallow bay: the Yatsushiro Sea, Japan. The developed model showed an excellent ability to reproduce the stratification and CO2 dynamics of the Yatsushiro Sea. Through numerical model simulations, we analyzed the annual CO2 dynamics in the Yatsushiro Sea in 2018. The results show that the effect of stratification on the CO2 dynamics in seawater varies greatly depending on the distance from the estuary and the period. In the estuarine region, stratification manifests itself throughout the year by promoting the maintenance of a high partial pressure of CO2 (pCO2) in surface waters, resulting in surface pCO2 being higher than atmospheric pCO2 for up to 40 days during the flood period (average surface pCO2 of 539.94 µatm). In contrast, in areas farther from the estuary, stratification mainly acts to promote the maintenance of high pCO2 in surface waters during periods of high freshwater influence. Then changes to a lower surface pCO2 before the freshwater influence leads towards complete dissipation. Finally, we estimated the FCO2 of the Yatsushiro Sea in 2018, and the results showed that the Yatsushiro Sea was a sink area for atmospheric CO2 in 2018 (−1.70 mmol/m2/day).